An ecological study of tropical butterflies in monoculture and polyculture oil palm agro ecosystems - Muslim, Siti Asmah (2016)
Commercial oil palm farming is growing rapidly and becoming common among small-scale farmers in the tropics. This is due to the global need of palm oil in various products and also, for providing sustainable income to farmers.However, land conversion into oil palm plantations and smallholdings has a major impact on biodiversity. In existing oil palm production landscapes, little is known on how farmland butterfly diversity is being affected by different farming practices. In this study, butterfly community under different farming practices in oil palm smallholdings, was investigated. To determine which farming practices supported more butterfly diversity, two different practices were assessed in this study. The first is the polyculture farming (mixed crop species including oil palm and banana) and the other being monoculture farming, which consists only oil palms crops. Polyculture smallholdings were predicted to be able to support greater butterfly biodiversity than monoculture smallholdings. Plant heterogeneity may increase niche diversity and appear as a host for a variety of butterflies. This study compared species richness and composition between monoculture and polyculture smallholdings. This study also determined habitat quality characteristics that are important for butterfly to maintain greater species richness. Butterflies were sampled using Van Someron–Rydon butterfly trap at 120 sites, where 60 sites were spatially replicated at monoculture and polyculture smallholdings. Contrary to initial prediction, our results showed there were no significant differences in species richness, abundance and composition of butterflies between the polyculture and monoculture smallholdings. The findings suggested that the adverse effects of monoculture farming on biodiversity can be mitigated in smallholding. This is by introducing structural and compositional habitat heterogeneity through the practice of polyculture farming. Habitat quality explained 32.1% of the variations in butterfly richness. In conclusion, oil palm production landscapes should feature multiple farming practices such as those implemented in smallholdings for improved conservation of butterfly diversity.